St Paul's epistles to the Colossians and to Philemon a revised text with introductions, notes and dissertations - Lightfoot, Joseph Barber, 1828-1889 (Grand Rapids, MI Zondervan, 1959)
Includes bibliographical references and index.
First published 1879.This is the tenth reprinting (1974) of this new ed.
Keywords: Bible. N.T. Colossians -- Greek text; Bible. N.T. Colossians -- commentaries; Bible. N.T. Philemon -- Greek text; Bible. N.T. Philemon -- commentaries